Development and application of indicators for the reduction of potentially preventable hospital admissions related to medications. (February 2014) - Warlé-van Herwaarden, Margaretha F; Valkhoff, Vera E; Teichert, Martina; Koffeman, Aafke R; 't Jong, Geert W; Sturkenboom, Miriam CJM; De Smet, Peter AGM
<x xml:space="preserve">Abstract</x> Objective: The Dutch HARM-Wrestling (HW) Task Force issued general and drug-specific recommendations aimed at reducing hospital admissions related to medication (HARMs). This study examines if the drug-specific recommendations could be converted into indicators that could be monitored in existing databases of general practitioner (GP) or community pharmacy (CP) data. The study also assesses the performance of these indicators before and during the official release of HW recommendations. Methods: HW recommendations were divided into sub-recommendations. We studied to what extent these were measurable as indicators based on available information in both databases. For each measurable indicator, performance between 2007 and 2010 was determined and possibilities for further improvement were estimated. Results: Thirty-four drug-specific HW recommendations were divided into 69 sub-recommendations, 32 of which were measurable as indicator in at least one of the databases. Application of these indicators between 2007 and 2010 showed that many of the indicators did not change over time. Possibilities for further improvement were estimated as moderate to major for 16/31 (52%) indicators measured in the GP database and 6/15 (40%) HW indicators measured in the CP database. Conclusions: Further implementation of the HW recommendations and development of additional monitoring methods are warranted to improve drug safety in outpatients.